Revenue losses from corporate tax avoidance: Estimations from the UNU-WIDER Government Revenue Dataset - Alessandro Chiari (Charles University in Prague, Institute of Economic Studies (IES), 2022)
Corporate profit shifting to tax havens negatively impacts corporate tax revenue, particularly in low-income countries. Two studies published in 2016 and 2018 have proven this correlation using data from 2013. In this paper, I use the most recent version of the UNU-WIDER Government Revenue Dataset (GRD) to estimate government revenue losses in 2019 and to observe possible changes associated with the release of the new dataset. My estimations indicate that global tax revenue losses in 2019 are around USD 480 billion, compared to USD 500 billion in 2013. In terms of GDP percentage, my estimations confirm the presence of a higher share of losses in low-income, and more generally, in non-OECD countries, and they show a higher intensity of tax avoidance practices in those countries. The results also suggest that the total level of tax revenue losses has plateaued, with no increase in losses occurring since 2013.
Keywords: F21; F23; H25; 330; international taxation; corporate income tax; tax avoidance; tax havens; base erosion; profit shifting; income inequality; developing countries